A quantitative morphological analysis of three-dimensional CT coxal bone images of contemporary Japanese using homologous models for sex and age estimation. (February 2019) - Biwasaka, Hitoshi; Aoki, Yasuhiro; Takahashi, Yusuke; Fukuta, Mamiko; Usui, Akihito; Hosokai, Yoshiyuki; Saito, Haruo; Funayama, Masato; Fujita, Sachiko; Takamiya, Masataka; Dewa, Koji
Highlights: Homologous model created from 3D CT enabled quantitative analysis of the coxal bone. Sex of 94% of the samples was correctly assigned by measuring point-to-point distances. Age-dependent principal components (PC) were detected with PC analysis of the models. Age-dependent morphological changes of the coxal bone were visualized by shifting PCs. Morphological disparity between right and left coxal bone was measured and visualized. Abstract: Sexual dimorphisms and age-dependent morphological features of the human coxal bone were quantitatively analyzed using homologous models created from three-dimensional (3D) computed tomography images of the pelvis (male: 514 samples, female: 388 samples, age 16–100). Bilateral average coxal images of each sex and age decade were generated separately through principle component analyses (PCA). By measuring average point-to-point distances of 8472 corresponding points (average corresponding point differences [ACPDs]) between each homologous coxal image and the average images, the sex of more than 93% of the samples was correctly assigned. Some principal components (PCs) detected in PCA of the homologous models of the samples correlated fairly well with age and are affected by features of the curvature of the iliac crest, the arcuate line and the greater sciatic notch. Moreover, separate PCA using the average images of each age decade successfully detected the first PCs, which were strongly correlated with age. However, neither multiple regression analysis using PCs related to age nor comparison of ACPDs with the average images of each age decade could produce accurate results for age decade assignment of unknown (blind) samples. Therefore, more detailed analysis of age-dependent morphological features would be necessary for actual age estimation. In addition, some laterality or left and right shape difference of the coxal bone images was also elucidated, and was more significant in females. Analysis of 3D structures using homologous models and PCA appears to be a potential technique to detect subsistent morphological changes of bones.